2022
DOI: 10.1002/celc.202200045
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Design of Fe−N4 Active Sites and Hierarchical Porosity in Hydrazine Oxidation Electrocatalysts

Abstract: Hydrazine is a promising energy-dense fuel for alkaline fuel cells. To design efficient and affordable electrocatalysts for the hydrazine oxidation reaction (HzOR), one needs to control both the active site and the supporting scaffold. We now report a family of electrocatalysts for alkaline HzOR, consisting of atomically dispersed FeÀ N 4 sites (as iron corroles of varying sizes) on hierarchically porous, electronically conductive carbon scaffolds that were prepared by self-templating from a novel barium-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…This contrasts all previously reported Fe–N–C HzOR electrocatalysts, where Fe is typically deactivated, resulting in a peak-shaped voltametric wave. 50,63,64 The atomical dispersion of the Fe–N x moieties is further supported by cyanide and nitrite poisoning experiments (Fig. S10, ESI†), which show lower current densities upon selective poisoning of iron centers.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…This contrasts all previously reported Fe–N–C HzOR electrocatalysts, where Fe is typically deactivated, resulting in a peak-shaped voltametric wave. 50,63,64 The atomical dispersion of the Fe–N x moieties is further supported by cyanide and nitrite poisoning experiments (Fig. S10, ESI†), which show lower current densities upon selective poisoning of iron centers.…”
Section: Resultsmentioning
confidence: 76%
“…This contrasts all previously reported Fe-N-C HzOR electrocatalysts, where Fe is typically deactivated, resulting in a peak-shaped voltametric wave. 50,63,64 The atomical dispersion of the Fe-N x moieties is further supported by cyanide and nitrite poisoning experiments (Figure S10), which show lower current densities upon selective poisoning of iron centers. 66,[86][87][88] Tafel analysis confirms a distinct change in electrocatalytic mechanism (Figure S11): the iron-free NC= materials show Tafel slopes of 270±70 mV/dec, whereas the iron-imprinted Fe-NC Ln catalysts exhibit steeper slopes of 140±25 mV/dec (Table S4).…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 74%
See 1 more Smart Citation
“…Shahaf et al demonstrated a range of novel orthogonally designed hydrazine oxidation electrocatalysts with iron corroles as molecular catalysts. 155 The iron(III) corroles that were tested are meso-C-substituted with CF 3 , C 6 F 5 , or 2,6difluorophenyl. These are listed in the order of electronwithdrawing capability, and the former complex is also much smaller than the other two.…”
Section: Oxygen Reduction Reaction Orrmentioning
confidence: 99%
“…HzOR electrocatalysis was since reported on many carbon-adsorbed metallo­phthalo­cyanines, while metallocorroles were tested most recently. Shahaf et al demonstrated a range of novel orthogonally designed hydrazine oxidation electrocatalysts with iron corroles as molecular catalysts . The iron­(III) corroles that were tested are meso -C-substituted with CF 3 , C 6 F 5 , or 2,6-difluorophenyl.…”
Section: Electrocatalysismentioning
confidence: 99%